Ontologi Manajemen Pendidikan Islam dalam Konstruksi Al-Qur’an dan Al-Hadits - Muhamad Fatih Rusydi Syadzili (STAI Ihyaul Ulum Gresik, 2019)
Management is a process of utilizing all resources through the help of others and cooperating with them, so that common goals can be achieved effectively, efficiently, and productively. The nature of Islamic management can be interpreted as a process of utilizing all available resources (Islamic Ummah, educational institutions or others) both hardware and software. Utilization is carried out through cooperation with others effectively, efficiently, and productively to achieve happiness and prosperity both in the world and the hereafter.